Pengaruh Return On Asset, Return On Equity, Net Profit Margin, Current Ratio, Debt To Equity Ratio Dan Debt To Asset Ratio Terhadap Pertumbuhan Laba Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2021-2023 - Yuliana, Rischa; Saraswati, Wiwik; Azizil Yudaruddin, Yanzil (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This study aims to examine the effects of Return On Asset, Return On Equity, Net Profit Margin, Current Ratio, Debt To Equity Ratio and Debt To Asset Ratio. The data used in this study is the annual financial statements of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The type of research used is quantitative research. The sampling technique uses the Purposive sampling method which produces 197 samples of the Company with the total population data obtained 251 from 3 periods. The data analysis methods used are descriptive statistical analysis and multiple linear regression analysis. The test tools used are the classical assumption test, the determination coefficient test and the t-test. The results of this study state that Return On Asset and Net Profit Margin have a significant effect on profit growth. Meanwhile, Return On Equity, Current Ratio, Debt To Equity Ratio and Debt To Asset Ratio did not have a significant effect on profit growth.